Genetic divergence analysis in turf grasses based on morphological traits - JANAKIRAM, T; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2014)
Despite of enhancing interest on turfs in India, all the available varieties of turf grasses in the country are being imported and are often poorly adapted to the prevailing climatic conditions. This prompted to begin a collection activity of turfgrass species, with the ultimate goal of identifying promising materials for further development of lawns suitable for various conditions. The present investigation conducted on eight species and four varieties of turf grasses depicted significant differences in all the growth related traits studied. All turf grasses under study exhibited fine leaf texture except Eragrostis curvula (Schrad.) Nees having medium coarse texture, Paspalum notatum Flugge and Argentine bahia having coarse texture and Poa pratensis L. which exhibited medium fine leaf texture. The Agrostis palustris L. exhibited maximum mean performance for shoot density/25 cm2 (277.33), whereas minimum was exhibited by Cynodon dactylon L. var Panama (57.67). The coefficient of variation was minimum for relative water content (GCV = 13.77, PCV = 14.60) and maximum for root length (GCV = 64.70, PCV = 66.46). Heritability estimates for all the traits were generally moderate to high. High heritability was observed for shoot density per 25 cm2 (98.00), whereas moderate heritability was observed for dry root/shoot ratio (64.12). High heritability along with high genetic advance was observed for shoot density per 25cm2 (h2 = 98.00, GA = 142.02) and germination percentage (h2 = 96.50, GA = 48.16).